THE STUDENTS’ PERCEPTION TOWARD FUN ENGLISH DAY - Ardhy Supraba; Muhammad Hasby; Juwita Crestiani; Sunardin, Sunardin; Rizal A.M. Sjachrun (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This research aims to find out the students’ perception toward fun English day. The population of this research is the third-year students of SMAN 2 Palopo. The sample of this research is selected through purposive sampling technique. One class represented as the sample that is class XII IPA 1. The result of this research shows that the students’ perception toward fun English day gained score 47 which is classified as very positive perception and most students stated that fun English day activity was very effective and excellent activity for the improvement and development of their English. Finally, the researcher concluded that fun English day was excellent activity for improving and developing the students’ English competence. In other words, most of them admitted that fun English day could effectively and significantly improve and develop their English.